2008
DOI: 10.1007/s00280-008-0842-3
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear receptor mediated induction of cytochrome P450 3A4 by anticancer drugs: a key role for the pregnane X receptor

Abstract: Purpose Induction of cytochrome P450 (CYP) 3A4, an enzyme that is involved in the biotransformation of more than 50% of all drugs, by xenobiotics is an important cause of pharmacokinetic drug-drug interactions in oncology. In addition to rifampicin and hyperforin, the anticancer drug paclitaxel has also been shown to be an inducer of CYP3A4 via activation of the pregnane X receptor (PXR). We therefore screened 18 widely used anticancer drugs for their ability to activate PXR-mediated CYP3A4 induction. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
59
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 22 publications
1
59
0
Order By: Relevance
“…Second, the time-dependent inhibition of CYP3A was actually substrate independent ( Figure 3). In the cell-based CYP3A activity assessment method by Harmsen et al, the cells were cultured in medium containing erlotinib for two consecutive days before measurement of the formation of 1'-hydroxymidazolam [16] . During the 2-d culture period, time dependent inhibition of CYP3A could occur, thus decreasing the formation of 1'-hydroxy midazolam.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the time-dependent inhibition of CYP3A was actually substrate independent ( Figure 3). In the cell-based CYP3A activity assessment method by Harmsen et al, the cells were cultured in medium containing erlotinib for two consecutive days before measurement of the formation of 1'-hydroxymidazolam [16] . During the 2-d culture period, time dependent inhibition of CYP3A could occur, thus decreasing the formation of 1'-hydroxy midazolam.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al found that erlotinib stimulated CYP3A-mediated midazolam metabolism in liver and intestinal microsomes [15] . Nevertheless, in a cell-based CYP3A activity assay, erlotinib was shown to decrease the formation of 1'-hydroxymidazolam, showing the potency to inhibit CYP3A activity [16] . As for the phase II enzymes, erlotinib was shown to exhibit inhibition activity on human UDP-glucuronosyltransferase (UGT) 1A1 [17] .…”
Section: Introductionmentioning
confidence: 99%
“…Given that DB was mainly metabolized by CYP3A4 in humans, higher expression of 3A, including 3A1 and 3A2, in male than in female mice and rats (Kato and Yamazoe, 1992) could enhance more metabolized DB, resulting in higher hepatotoxicity in male mice and lower oral bioavailability in male rats than in females. Concerning drug interaction, it should be noted that D. bulbifera may cause fatal toxicity when used with inducers of CYP3A4 such as rifampicin and hyperforin that also induce CYP2C9 expression (Chen et al, 2004;Harmsen et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…However, this treatment is not always successful and often unwanted pharmacological effects occur in cancer patients, such as unresponsiveness or toxicity. A common cause for these unpredictable effects is up and down regulation of drug transporters or drug-metabolizing enzymes such as cytochrome P450 (Harmsen et al, 2009;Chen et al, 2010). Of these enzymes, CYP3A4 is quantitatively the most important because it metabolizes more than 50% of all drugs and the majority of the currently prescribed anticancer drugs (Anzenbacher and Anzenbacherová, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Cancer patients are often treated with multiple anticancer drugs or hormonal agents in combination with supplemental therapies to treat or prevent side effects (Harmsen et al, 2009). However, this treatment is not always successful and often unwanted pharmacological effects occur in cancer patients, such as unresponsiveness or toxicity.…”
Section: Introductionmentioning
confidence: 99%